2021
DOI: 10.3389/fmicb.2021.700434
|View full text |Cite
|
Sign up to set email alerts
|

DHAV-1 Blocks the Signaling Pathway Upstream of Type I Interferon by Inhibiting the Interferon Regulatory Factor 7 Protein

Abstract: Duck hepatitis A virus (DHAV), which mainly infects 1- to 4-week-old ducklings, has a fatality rate of 95% and poses a huge economic threat to the duck industry. However, the mechanism by which DHAV-1 regulates the immune response of host cells is rarely reported. This study examined whether DHAV-1 contains a viral protein that can regulate the innate immunity of host cells and its specific regulatory mechanism, further exploring the mechanism by which DHAV-1 resists the host immune response. In the study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that the DHAV-1 3C protein can inhibit the IFNβ upstream signaling pathway by targeting the IRF7 protein [ 26 ]. The presence of 3CD protein as a precursor to 3C protease and 3D polymerase is unclear as to whether it also has the immune evasion function of 3C protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the DHAV-1 3C protein can inhibit the IFNβ upstream signaling pathway by targeting the IRF7 protein [ 26 ]. The presence of 3CD protein as a precursor to 3C protease and 3D polymerase is unclear as to whether it also has the immune evasion function of 3C protein.…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotic cells, protein degradation pathways are mainly divided into the autophagy-lysosomal pathway, proteasome pathway, and caspase-dependent pathway [ 27 ]. To determine whether these protein degradation pathways play a role in the DHAV-1 3CD-induced reduction of RIG-I, the proteasome inhibitor MG132, the autophagy inhibitor 3-MA, the lysosomal inhibitor NH 4 Cl, and the broad-spectrum caspase inhibitor Z-VAD-FMK were used to assess the inhibitory effect and it has been shown that these inhibitors did not affect cellular activity [ 26 ]. Cells were transfected with 3CD-HA and RIG-I(N-terminal)-Flag and maintained in the presence or absence of the inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Picornaviruses, including DHAV-1 have evolved immune evasion mechanisms to suppress the host cell's innate immune response ( Zhang et al, 2020 ). They can inhibit the expression of critical receptors involved in the immune response, including TLR3, TLR7, MDA5, RIG-I, and NLRP3 ( Xie et al, 2018 ; Lai et al, 2021 ). It is well established that TLR-7 is a crucial PRR that recognizes single-stranded RNA viruses and is primarily involved in initiating the innate defense against DHAV-1 infection, thereby generating proinflammatory cytokines and IFNs ( Mao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…DHAV-1 employs an immune evasion strategy in host cells by inhibiting PRRs ( Xia et al, 2023 ). This evasion tactic hinders the natural IFN-mediated antiviral immunity and facilitates DHAV-1 replication ( Lai et al, 2021 ). In the current study, we revealed a significant ( P < 0.05) finding of a pronounced downregulation of IFN-α and IFN-β expression levels in the positive control group (G2) at 48 hpi, accompanied by an increase in DHAV-1 copies.…”
Section: Discussionmentioning
confidence: 99%